Effect of microbe and irradiation on quality transformation of raw Pu’er tea during storage - TIAN Xuefeng; YAO Yao; TANG Yi (浙江大学学报. 农业与生命科学版, 2021)
This study focused on the effects of irradiation, artificial microbe treatment, temperature and humidity control on the aging and transformation of raw Pu’er tea, and explored the relationship between the factors such as microorganisms, irradiation and the quality of raw Pu’er tea. The results showed that the water content of tea samples during storage was between 7.0% and 9.0%, and the microbial changes of tea samples were not regular. Aqueous extract, free amino acid, tea polyphenol, catechin components showed a consistent change trend among different treatments. The contents of amino acids and tea polyphenols in the irradiated 9 kGy tea samples stored under the room temperature and 30 ℃ decreased more after 200 d, with the decline range of 40.37%, 38.82% and 37.65%, 36.73%, respectively, and the sensory quality was significantly lower than the aseptic treatments. The treatment A2B2C1 namely irradiated 5 kGy sterile tea samples stored at 30 ℃ and 70% humidity had better sensory quality. The quality of tea samples treated with microbe after irradiation was improved with the extension of storage time and was superior to that treated without irradiation.But the sterile treatments under the same irradiation condition still had better overall flavor performance.The above results indicate that the microbial involvement has no direct effect on the quality of raw Pu’er tea under the storage conditions of this study.However, the irradiation treatment with its radiochemical oxidation has an obvious effect on the aging and transformation of raw Pu’er tea.